The Effect of Compensation, Work Environment and Career Development on Work Motivation of Teachers at The Bahagia Banyak Berkat Foundation, Sawah Besar - Central Jakarta - Noviherni; Elon Manurung; Rivaldy (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study aims to empirically test the effect of compensation, work environment, and career development on work motivation among teaching staff at the Bahagia Banyak Berkat Foundation, Sawah Besar, Central Jakarta. Background of the Problem: In 2023, the average level of motivation of teaching staff at various levels of education is in the high category, with changes in the learning and teaching system in schools in Indonesia due to following the direction of the government and the minister of education. Novelty: Analyzing the same variables but focusing on teacher performance as a research sample. Research Method: The study uses primary data, the sample of this study is 35 respondents by testing Compensation, Work Environment, and Career Development on Work Motivation and using descriptive analysis and Structural Equation Model (SEM-PLS). Findings/Results: That compensation, work environment, and career development do not have a significant effect on work motivation among teaching staff at the Bahagia Banyak Berkat Foundation, Sawah Besar, Central Jakarta. Conclusion: There are no factors that influence work motivation, so further studies are needed on compensation, work environment, and career development in increasing motivation in other sectors.